New Modes of Subjectivation: the Experience of “Mujeres Libres” in the Spanish Revolution - Rago, Margareth (Revista Estudos Feministas, 2008)
This article focuses on the experience of one of the major mass women´s movement during the Spanish Revolution, the anarchist and feminist organization “Free Women”. It considers Foucault´s concepts as well as feminist criticism relating to ethics and subjectivity as the main theoretical references. In the context of a revolutionary movement, that started in Spain in the thirties, the organization aimed at achieving feminine emancipation. It understood clearly the importance of creating new modes of subjectivation, in this highly conservative, religious and male country.